Immune responses following experimental infection with Ascaridia galli and necrotic enteritis in broiler chickens. Issue 6 (2nd November 2017) - Ruhnke, Isabelle; Andronicos, Nicholas Matthew; Swick, Robert A.; Hine, Brad; Sharma, Nisha; Kheravii, Sarbast K.; Wu, Shu-Biao; Hunt, Peter
ABSTRACT: Broilers commonly suffer from necrotic enteritis (NE). Other gastrointestinal infectious diseases affect poultry, including nematode infections which are considered a re-emerging disease in barn and free-range systems. The aim of this study was to characterize the immune response of broilers after artificial infection with NE and contrast these with responses to the nematode Ascaridia galli and determine whether immune parameters measured during the course of infection can be used to distinguish infected from uninfected birds. A total of 96 one-day-old male Ross 308 broiler chickens were used in this study. At 10 days of age, broilers were randomly assigned to one of the following treatment groups: control birds ( n = 32), A. galli infected birds ( n = 32), or NE infected birds ( n = 32) and inoculated with the appropriate infective agents. The immune response of birds was monitored through evaluation of haematology parameters, acute phase protein production, and intraepithelial intestinal lymphocyte population changes at 11, 16, 20, and 32 days of age. T-helper cells (CD4 + CD8 − ) increased significantly over time, and were significantly higher in A. galli and NE compared to day 10 controls. In conclusion, α-1 glycoprotein levels can distinguish birds with NE from other birds, including those infected with A. galli ; also T-helper cell numbers can distinguish both NE and A. galli from uninfected birds and thirdly, 10 days post infection is the best time point to evaluate the bird's immune response for A. galli infections.